Fine Mapping of a Vigor QTL in Chickpea (Cicer arietinum L.) Reveals a Potential Role for Ca4_TIFY4B in Regulating Leaf and Seed Size - Nguyen, Duong T.; Hayes, Julie E.; Harris, John; Sutton, Tim (Frontiers in Plant Science, 2022)
Plant vigour is a complex trait for which the underlying molecular control mechanisms remain unclear. Vigorous plants tend to derive from larger seeds and have greater early canopy cover, often with bigger leaves. Here, we delimited the size of a major vigour QTL on chickpea chromosome 4 to 104.4kb, using recombinant association analysis in 15 different heterozygous inbred families, derived from a Rupali/Genesis836 recombinant inbred line population. Phenotypic and molecular genetic analysis provided evidence for a role of the gene Ca4_TIFY4B, in determining leaf and seed size in chickpea. A nonsynonymous SNP in the high-vigour parent was located inside the core motif TIFYCG, resulting in a residue change T[I/S]FYCG. Complexes formed by orthologues of Ca4_TIFY4B (PEAPOD in Arabidopsis), Novel Interactor of JAZ (CaNINJA), and other protein partners, are reported to act as repressors regulating transcription of downstream genes that control plant organ size. When tested in a yeast 2-hybrid assay, this residue change suppressed the interaction between Ca4_TIFY4B and CaNINJA. This is the first report of a naturally occurring functional variant of the TIFY family in plants, and we provide a robust gene-derived molecular marker for selection in chickpea for seed and plant organ size – key component traits of vigour.